The Influence of Tourist Attitudes in Buying Food Souvenirs on Satisfaction and Purchase Intention - Eni Karsiningsih; Muhammad Soleh Rafsanjani (International Journal of Business and Quality Research, 2023)
Tourists are showing an increasing interest in locally produced food and bringing it home as souvenirs. One of the souvenirs that can be brought home is food souvenirs. This study aims to examine the relationship between attitudes towards satisfaction and tourists' purchase intentions. The research method uses a quantitative method approach. Data collection was carried out using a purposive sampling technique using a questionnaire. The number of respondents who were used as research samples was 200 tourists. Research respondents were domestic tourists who shopped for food souvenirs and were willing to fill out a questionnaire. The analysis technique used is the Structural Equation Model with Partial Least Square. Data analysis using SmartPLS software. The results of the study show that attitude directly has a positive and significant effect on satisfaction and purchase intention. Satisfaction also has a direct and significant effect on purchase intention. In addition, attitudes have an indirect effect on purchase intentions through satisfaction. These findings provide opportunities for food souvenir businesses to develop marketing strategies that satisfy tourists so as to increase tourists' buying intentions for food souvenirs.